(untitled) (Journal of the College of Basic Education, 2023)
Summary of the research:The project subject is one of the common subjects for all colleges and institutes of all specializations, as each student must submit a graduation project of his own, and this is done through the student’s agreement with one of the teachers of the subjects that were studied for the previous years and within the field that the student intends to work on in his graduation project. The project also includes employing most of the specialized subjects that he studied to come up with an integrated project that represents one of the most important outputs of the teaching and learning processes in which the student spent his school years. From here, the idea of teaching the project material for the second stage, Department of Textile Design Techniques, was born at the Institute of Applied Arts, according to the theory of formal art education to benefit from it and the broad horizons it bears that give the student the freedom to choose the theoretical scientific material and apply the study of those materials in a practical way. Where a teaching unit for students was designed by the researcher. Its implementation took a full academic year, during which students were taught the four fields of formal art education, which are (aesthetics, art criticism, art history, and artistic production) according to the students’ needs and interests, and after implementing the teaching unit in all its details. Their project, which represents a plastic artistic product (painting), was completed using the canvas surface and acrylic colors. The subject of the artistic production was formulated according to what the students studied of the scientific material for the four fields of theory. To embody in its content a mixture of the three civilizations that have been studied, namely the Mesopotamian civilization, the Pharaonic civilization, and the African civilization.key words :formal art education theory; employment; The project; aesthetics; art criticism; art history; Technical production.applied